Function of the ς(E) Regulon in Dead-Cell Lysis in Stationary-Phase Escherichia coli - Nitta, Takeshi (American Society for Microbiology, 2000)
Elevation of active ς(E) levels in Escherichia coli by either repressing the expression of rseA encoding an anti-ς(E) factor or cloning rpoE in a multicopy plasmid, led to a large decrease in the number of dead cells and the accumulation of cellular proteins in the medium in the stationary phase. The numbers of CFU, however, were nearly the same as those of the wild type or cells devoid of the cloned gene. In the wild-type cells, rpoE expression was increased in the stationary phase and a low-level release of intracellular proteins was observed. These results suggest that dead cell lysis in stationary-phase E. coli occurs in a ς(E)-dependent fashion. We propose there is a novel physiological function of the ς(E) regulon that may guarantee cell survival in prolonged stationary phase by providing nutrients from dead cells for the next generation.